Physical and physiological attributes of soccer goalkeepers - Should we rely only on means and standard deviations? - Nikolaidis, P.; Ziv, G.; Arnon, M.; Lidor, R. (Journal of Human Sport & Exercise, 2015)
The purpose of this study was twofold: (a) to profile physical characteristics and physiological attributes of soccer goalkeepers (GKs) who were divided into three age groups - under 16 years, 16-19, and over 19, and (b) to examine the intra-individual variability among the GKs in each age group on all physical and physiological measurements performed in the study. The GKs underwent a series of physical (e.g., height, body mass, and percentage of body fat) and physiological (e.g., anaerobic profile, power and strength, and flexibility) tests. The three main findings of the current study were: (a) differences in physical characteristics and physiological attributes existed between GKs in the three age groups, (b) intra-individual variability can be found in most physical characteristics and physiological attributes of the GKs, and (c) the intra-individual variability was observed in all three groups. These findings emphasize the need for coaches to examine the intra-individual variability in GKs on their teams. These findings can be used by coaches when planning specific training programs for GKs of different age and skill levels.